Insights into Bacteriophage Application in Controlling Vibrio Species - Letchumanan, Vengadesh; Chan, Kok-Gan; Pusparajah, Priyia; Saokaew, Surasak; Duangjai, Acharaporn; Goh, Bey-Hing; Ab Mutalib, Nurul-Syakima; Lee, Learn-Han (Frontiers in Microbiology, 2016)
Bacterial infections from various organisms including Vibrio sp. pose a serious hazard to humans in many forms from clinical infection to affecting the yield of agriculture and aquaculture via infection of livestock. Vibrio sp. is one of the main foodborne pathogens causing human infection and is also a common cause of losses in the aquaculture industry. Prophylactic and therapeutic usage of antibiotics has become the mainstay of managing this problem, however this in turn led to the emergence of multidrug resistant strains of bacteria in the environment; which has raised awareness of the critical need for alternative non antibiotic based methods of preventing and treating bacterial infections. Bacteriophages - viruses that infect and result in the death of bacteria – are currently of great interest as a highly viable alternative to antibiotics. This article provides an insight into bacteriophage application in controlling Vibrio species as well underlining the advantages and drawbacks of phage therapy.